2009
DOI: 10.1088/0957-4484/20/24/245604
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous silicon thin films obtained by plasma-enhanced chemical vapor deposition using dichlorosilane as silicon precursor

Abstract: Polymorphous silicon thin films (pm-Si) have been deposited from mixtures of dichlorosilane and hydrogen, using argon as the diluting gas by plasma-enhanced chemical vapor deposition. The deposition conditions were chosen to simultaneously obtain both Si nanocrystallites and an amorphous silicon matrix in the as-grown samples. High resolution transmission electron microscopy studies show the crystallinity of Si domains whose dimensions are in the interval of 2-14 nm. The surface passivation state of the silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…[1,2] In order to fabricate the thin films for specific application needs, several approaches have been proposed, and it has been reported that doping and nanocrystallization of the films are two effective methods. [3,4] Raman spectroscopy has been used extensively to study the structure of the materials. [5,6] However, a systematic Raman study of the structural evolution of Si : H thin films deposited by plasma-enhanced chemical vapor deposition (PECVD) under different deposition conditions has not been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In order to fabricate the thin films for specific application needs, several approaches have been proposed, and it has been reported that doping and nanocrystallization of the films are two effective methods. [3,4] Raman spectroscopy has been used extensively to study the structure of the materials. [5,6] However, a systematic Raman study of the structural evolution of Si : H thin films deposited by plasma-enhanced chemical vapor deposition (PECVD) under different deposition conditions has not been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…(v) Chemical vapor deposition method : In this scheme chemical reactions are induced through a plasma usually generated by radio frequency or direct current discharge . By controlling the reaction parameters, good quality films can be obtained from vapor containing the chemical species used as precursors in the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some critical issues that remain to be addressed to achieve the best performance of pm-Si in a photovoltaic device: (i) control of the nanocrystallite size distribution and density in the amorphous matrix which determines the optoelectronic properties of pm-Si, (ii) control of the hydrogen incorporation in the films and Medium Range Order (MRO) of the amorphous matrix to minimize the Staebler-Wronski effect, and (iii) optimization of the processing of pm-Si thin Raman shift (cm −1 ) films to comply with the requirements of the photovoltaic industry. Previously, we have reported the growth of different silicon alloys by plasma enhanced chemical vapor deposition (PECVD) using dichlorosilane (SiH 2 Cl 2 ) as silicon precursor [10][11][12]. Due to the chlorine chemistry introduced in the deposition process, it is possible to obtain nanocrystalline silicon inclusions at low deposition temperatures and regulate the hydrogen content of the films, leading to an increased chemical stability of the material.…”
Section: Introductionmentioning
confidence: 99%